Influenza vaccine supply chain with vaccination promotion effort and its coordination. Issue 1 (2nd January 2017) - Yan, Xinghao; Zaric, Gregory S.
ABSTRACT: We develop an influenza vaccination supply chain model consisting of a health authority, a vaccine manufacturer, and the population. The health authority determines the order quantity and the cos to increase the vaccination rate; the manufacturer determines the production effort, subject to random yield; and the population determines the vaccination probability, which depends on the health authority's promotion effort and the realized vaccine supply. We find that the population has limited incentive to vaccinate due to free riding when there is no vaccine shortage, but has full incentive when there is a vaccine shortage. The manufacturer and the health authority have lower incentives for production and vaccine demand promotion in a decentralized system than in a centralized system. However, the health authority may pursue an aggressive ordering strategy in which the order quantity may be even higher than the level leading to herd immunity. We show that an outcome-based coordinating contract in which the payment depends on the number of infections cannot take a simple linear format. However, even with very limited verifiable information, a contract with a simple linear or piecewise linear format with respect to order quantity can achieve coordination under a wide range of vaccine prices.